Translation, Cross-Cultural Adaptation, and Measurement Properties of the Portuguese Version of the Global Trigger Tool for Adverse Events - Pierdevara L; Porcel-Gálvez AM; Ferreira da Silva AM; Barrientos Trigo S; Eiras M (Dove Medical Press, 2020)
Ludmila Pierdevara,1 Ana María Porcel-Gálvez,2 Alexandra Maria Ferreira da Silva,1 Sérgio Barrientos Trigo,3 Margarida Eiras4 1Escuela Internacional de Doctorado, Universidad de Sevilla, Sevilla, Spain; 2Nursing Department, Escuela Internacional de Doctorado, University of Seville, Sevilla, Spain; 3Department of Nursing, Escuela Internacional de Doctorado, University of Seville, Sevilla, Spain; 4H&RC ESTeSL-IPL, Lisbon, PortugalCorrespondence: Ludmila Pierdevara Praça do Poder Local, Lote 7ª, 6º Frente, Lagos 8600-524, PortugalTel +351 963605271Email pierdevara@hotmail.comPurpose: To adapt and validate the Global Trigger Tool (IHI-GTT), which identifies and analyzes adverse events (AE) in hospitalized patients and their measurement properties in the Portuguese context.Methods: A retrospective cross-sectional study was based on a random sample of 90 medical records. The stages of translation and cross-cultural adaptation of the IHI-GTT were based on the Cross-Cultural Adaptation Protocol that originated from the Portuguese version, GTT-PT, for the hospital context in medical-surgical departments. Internal consistency, reliability, reproducibility, diagnostic tests, and discriminatory predictive value were investigated.Results: The final phase of the GTT-PT showed insignificant inconsistencies. The pre-test phase confirmed translation accuracy, easy administration, effectiveness in identifying AEs, and relevance of integrating it into hospital risk management. It had a sensitivity of 97.8% and specificity of 74.8%, with a cutoff point of 0.5, an accuracy of 83%, and a positive predictive value of 69.8% and a negative predictive value of 0.98%.Conclusion: The GTT-PT is a reliable, accurate, and valid tool to identify AE, with robust measurement properties.Keywords: medical errors, patient safety, risk management